Organizational Culture and Knowledge Sharing Drive Employee Performance at Pertamina Patra Niaga: Budaya Organisasi dan Pembagian Pengetahuan Memengaruhi Kinerja Karyawan di Pertamina Patra Niaga - Prayuanto, Romadhon Febryan; Sriyono, Sriyono (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Human capital serves as the primary pillar for achieving corporate vision and mission, mandating the continuous focus on improving the quality and performance of employees. Specific Background As a leading oil processing company, PT Pertamina Patra Niaga is highly dependent on effective employee performance, where factors like organizational culture and knowledge sharing are considered crucial for competitive advantage. Knowledge Gap Previous studies show conflicting results, with some indicating no significant correlation between organizational culture and knowledge sharing with employee performance, establishing a clear research gap. Aims This study re-validates and refines the conceptual framework to test the combined positive and significant relationship of organizational culture and knowledge sharing on employee performance. Utilizing a quantitative survey with 384 employees, Results the findings confirm that both organizational culture and knowledge sharing positively and significantly drive the performance of PT Pertamina Patra Niaga employees. Novelty This research provides an updated, unified conclusion, resolving the contradictions in earlier studies within the context of a key Indonesian state-owned enterprise. Implications The results suggest that fostering a strong corporate culture and actively promoting information exchange are critical strategic levers for enhancing performance in the oil and gas sector. Highlights Organizational culture is a positive driver of employee performance. Knowledge sharing significantly correlates with better work outcomes. The research utilized a quantitative survey approach with 384 respondents. Keywords: Organizational Culture, Knowledge Sharing, Employee Performance, Quantitative Survey, PT Pertamina Patra Niaga